Tuberculosis Immunodiagnosis System: Analysis of Potential Losses of Patients for Registration - S. A. Sterlikov; T. N. Kаzykinа (Туберкулез и болезни лёгких, 2022)
The objective: to develop proposals to improve the effectiveness of the tuberculosis immunodiagnosis system in children by analyzing potential losses of patients for registration.Materials: data from primary medical records of 605 children in 5 regions of Russia, results of the survey in 513 legal guardians and 27 experts.Results. 13.9% of the children subject for screening were not examined, tests were administered in 1.1% of children who had contraindications to them, errors in the test administration were expected in 1.5% of children, and in 6.2% of children, antihistamine medications were used leading to errors in the detection of tuberculosis infection. In 3.7% of children, results of the test were not assessed, 3.1% of eligible children were not referred to the phthisiologist, and 6.5% were lost to follow-up by the phthisiologist.Conclusions. The cumulative loss during immunodiagnosis of tuberculosis made 68.7%. The main reasons for the losses are medical exceptions and refusals to have immunodiagnosis of tuberculosis by legal guardians, incomplete follow-up by the phthisiologist, and the use of antihistamines.To reduce these losses, it is advisable to consider the following: organizing consultation with the phthisiologist at children's polyclinics and large children's groups; legal guardians should be able to have a paid sick leave on the days when the child has an appointment with the phthisiologist; specifying indications for desensitizing therapy and prohibiting it outside the indications; organizing internal and external quality control system for immunodiagnostics.